Neuron‐specific caveolin‐1 overexpression improves motor function and preserves memory in mice subjected to brain trauma. Issue 8 (19th September 2017) - Egawa, Junji; Schilling, Jan M.; Cui, Weihua; Posadas, Edmund; Sawada, Atsushi; Alas, Basheer; Zemljic‐Harpf, Alice E.; Fannon‐Pavlich, McKenzie J.; Mandyam, Chitra D.; Roth, David M.; Patel, Hemal H.; Patel, Piyush M.; et al.
ABSTRACT: Studies in vitro and in vivo demonstrate that membrane/lipid rafts and caveolin (Cav) organize progrowth receptors, and, when overexpressed specifically in neurons, Cav‐1 augments neuronal signaling and growth and improves cognitive function in adult and aged mice; however, whether neuronal Cav‐1 overexpression can preserve motor and cognitive function in the brain trauma setting is unknown. Here, we generated a neuron‐targeted Cav‐1–overexpressing transgenic (Tg) mouse [synapsin‐driven Cav‐1 (SynCav1 Tg)] and subjected it to a controlled cortical impact model of brain trauma and measured biochemical, anatomic, and behavioral changes. SynCav1 Tg mice exhibited increased hippocampal expression of Cav‐1 and membrane/lipid raft localization of postsynaptic density protein 95, NMDA receptor, and tropomyosin receptor kinase B. When subjected to a controlled cortical impact, SynCav1 Tg mice demonstrated preserved hippocampus‐dependent fear learning and memory, improved motor function recovery, and decreased brain lesion volume compared with wild‐type controls. Neuron‐targeted overexpression of Cav‐1 in the adult brain prevents hippocampus‐dependent learning and memory deficits, restores motor function after brain trauma, and decreases brain lesion size induced by trauma. Our findings demonstrate that neuron‐targeted Cav‐1 can be used as a novel therapeutic strategy to restore brain function and prevent trauma‐associated maladaptive plasticity.—Egawa, J., Schilling, J. M., Cui, W., Posadas, E., Sawada, A., Alas, B., Zemljic‐Harpf, A. E., Fannon‐Pavlich, M. J., Mandyam, C. D., Roth, D. M., Patel, H. H., Patel, P. M., Head, B. P. Neuron‐specific caveolin‐1 overexpression improves motor function and preserves memory in mice subjected to brain trauma. FASEB J . 31, 3403–3411 (2017). www.fasebj.org